Management and documentation of pneumonia - a comparison of patients consulting primary care and emergency care - Louise Arntsberg; Sara Fernberg; Ann-Sofie Berger; Katarina Hedin; Anna Moberg (Taylor & Francis Group, 2024)
AbstractPatients may attend either primary or emergency care without referral in Sweden. Guidelines recommend a severity assessment, including assessment of vital signs, to be performed for all patients presenting with suspected pneumonia.Objective To compare management and documentation of vital signs, symptoms and infection severity in pneumonia patients seeking primary care and emergency care without referral.Design Medical record review of vital signs, examination findings and severity of pneumonia.Setting Primary and emergency care.Subjects Two hundred and forty patients diagnosed with pneumonia.Main outcome measures Vital signs, examination findings and severity of pneumonia. Assessments of pneumonia severity according to the reviewers, the traffic light score and CRB-65.Results Respiratory rate, blood pressure, heart rate and oxygen saturation were less often documented in primary care (p < .001). Chest X-ray was performed in 5% of primary care patients vs. 88% of emergency care patients (p < .01). Primary care patients had longer symptom duration, higher oxygen saturation and lower respiratory rate. In total, the reviewers assessed 63% of all pneumonias as mild and 9% as severe. The traffic light scoring model identified 11 patients (9%) in primary care and 53 patients (44%) in emergency care at high risk of severe infection.Conclusions Vital signs were documented less often in primary care than in emergency care. Patients in primary care appear to have a less severe pneumonia, indicating attendance to the correct care level. The traffic light scoring model identified more patients at risk of severe infection than CRB-65, where the parameters were documented to a limited extent.